Malay paleography: A preliminary survey - Wan Mamat, Wan Ali @ Wan Yusoff (2011)
The origin and development of the Malay art of writing after the introduction of Islam into the Malay Archipelago were closely related to Arabic and Islamic traditions of writing. Almost all the Malay manuscripts extant were written in the Jawi script, the traditional script of the Malays which were developed based on the Arabic script, with a few additional letters, some borrowed from Farsi and others developed locally, in order to meet the needs of the Malay tongue. Etymologically, many of the Malay terms relating to the art of writing originated from Arabic words: huruf from huruf, kertas from qartas and dakwat from da’wat. In addition, the great majority of the Jawi manuscripts were translations or adaptations from Arabic books on Islam, biographies and stories of Islamic leaders and heroes and some adaptations from Persian and Indian legends and literature. This shows the extent of the influence of Islamic tradition of writing, especially Arabic, on Malay writing and scholarship